Enhancing university's brand performance during the COVID-19 outbreak: The role of ICT orientation, perceived service quality, trust, and student's satisfaction - Muhammad Amir Chaudhary; Naveed Iqbal Chaudhary; Alina Zulfiqar Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The purpose of this study is to examine the effect of information & communication technology (ICT) orientation on university's brand performance along with the mediating role of student's satisfaction and moderating role of trust and perceived service quality in times of COVID-19. To achieve this purpose, a quantitative methodological approach was adopted in which the data was collected online through 417 structured questionnaires from university students of Pakistan. The data was analyzed using SPSS and AMOS in which structural equation modeling was performed for testing hypotheses of the study. Results of the current study indicate that the ICT orientation has a significant positive effect on student's satisfaction and university's brand performance while the student's satisfaction significantly mediates the relationship between ICT orientation and university's brand performance. It has been further found that the perceived service quality acts as a significant but negative moderator in the relationship between ICT orientation and student's satisfaction. Results further reveal that the trust acts as a positive moderator in the relationship between student's satisfaction and university's brand performance. The current studyis expected to be an important contribution to the literature and practice as it provides useful implications that how universities can enhance and maintain their brand performance and student's satisfaction during the COVID-19 outbreak by adopting techniques and tools of ICT.
Keywords: 330; information & communication technology (ICT) orientation; perceived service quality; student's satisfaction; trust; university's brand performance; higher education; coronavirus(COVID-19)